Technostress pada perawat dan instrumen pengukurannya: Tinjauan sistematis - Enggriani, Yesica Tria; Handiyani, Hanny; Kuntarti, Kuntarti (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: The use of information technology is increasingly widespread in the health sector, especially for nurses. The intensity of the use of this technology has created a new phenomenon called technostress. The European Risk Observatory categorizes technostress as an increasing occupational health risk caused by the negative psychosocial effects of the use of information technology. These problems are correlated with decreased job satisfaction, productivity, and work-life balance that have the potential to threaten patient safety. Purpose: To analyze the dimensions, measurement instruments, and research results of technostress in nurses. Method: A systematic review was conducted by searching the literature related to technostress in nurses using PubMed, ScienceDirect, EBSCO, Proquest, and Scopus databases. Studies that met the inclusion criteria were assessed using the JBI Critical Appraisal Checklist for Cross-sectional Studies. Results: A total of seven relevant studies were identified with five high-quality studies and two moderate-quality studies. Five main dimensions of technostress were identified: techno-overload, techno-invasion, techno-complexity, techno-insecurity, and techno-uncertainty. Six measurement instruments were identified with moderate levels of technostress in nurses. Conclusion: Based on the results of the study review, six main instruments were obtained that were used to measure technostress in nurses and five main dimensions of technostress in nurses, including techno-overload, techno-invasion, techno-complexity, techno-insecurity, and techno-uncertainty, as well as moderate levels of technostress to impacts that include emotional exhaustion, work-privacy conflict, burnout, decreased job satisfaction, desire to move, and physical and mental health problems. Keywords: Measurement Instruments; Nurses; Technostress. Pendahuluan: Penggunaan teknologi informasi semakin meluas di sektor kesehatan, terutama pada perawat. Intensitas penggunaan teknologi ini telah menciptakan fenomena baru yang disebut technostress. European Risk Observatory mengategorikan technostress sebagai risiko kesehatan kerja yang terus meningkat yang diakibatkan efek psikososial negatif dari penggunaan teknologi informasi. Permasalahan tersebutlah yang berkorelasi dengan penurunan kepuasan kerja, produktivitas, dan keseimbangan kehidupan kerja yang berpotensi mengancam keselamatan pasien. Tujuan: Untuk menganalisis technostress pada perawat dan instrumen pengukurannya. Metode: Penelitian tinjauan sistematis terkait technostress pada perawat, pencarian literatur berasal dari database antara lain PubMed, ScienceDirect, EBSCO, Proquest, dan Scopus. Studi yang memenuhi kriteria inklusi dinilai menggunakan JBI Critical Appraisal Checklist for Cross-sectional Studies. Hasil: Sebanyak tujuh studi relevan diidentifikasi dengan lima studi berkualitas tinggi dan dua studi berkualitas sedang. Lima dimensi utama technostress teridentifikasi: techno-overload, techno-invasion, techno-complexity, techno-insecurity, dan techno-uncertainty. Enam instrumen pengukuran teridentifikasi dengan tingkat technostress moderat pada perawat. Simpulan: Berdasarkan hasil tinjauan studi, diperoleh sebanyak enam instrumen utama yang digunakan untuk mengukur technostress pada perawat dan lima dimensi utama technostress pada perawat yang meliputi, techno-overload, techno-invasion, techno-complexity, techno-insecurity, dan techno-uncertainty, serta tingkat technostress moderat hingga dampak yang meliputi kelelahan emosional, konflik kerja-privasi, burnout, penurunan kepuasan kerja, keinginan berpindah, serta masalah kesehatan fisik dan mental. Kata Kunci: Instrumen Pengukuran; Perawat; Technostress.